Analisis Perbandingan Pengalaman Pengguna Aplikasi Snapchat dan Aplikasi Instagram menggunakan User Persona dan Kuesioner Mecue - Wahyu Al Kindy; Retno Indah Rokhmawati; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Social media as an online media with its users can easily participate, share and create content through blogs, social networks, wikis, forums and the virtual world. Instagram and Snapchat provide a relatively similar user experience. User experience is how an internet user accesses a website or application, an experience they get from the website or application or in the world of IT is often referred to as User Experience (UX). This study aims to analyze the comparative experiences of users of Instagram and Snapchat applications using the meCUE questionnaire and look for the advantages and disadvantages of both applications. The meCUE questionnaire is a tool that is useful for evaluating the user experience or UX of a website or application. To reassure the feasibility of content, content and grammar in the world of User Experience, in this study re-validation of the meCUE questionnaire instrument with two experts was User Experience. After getting the validated questionnaire again, the questionnaire was distributed to 58 respondents who matched the criteria, specifically those who had used the Instagram and Snapchat applications, or who often used the two applications. The meCUE questionnaire has 5 modules and 10 assessment instruments in it, instruments include usefulness, usability, visual aesthetic, status, commitment, positive emotions, negative emotions, product loyalty, intention to use and overall evaluation, in this study there are objective data and subjective data . This study resulted in a comparison of the average value of each meCUE instrument for both applications where the Instagram application produced a higher average value than the Snapchat application and a comparison table of the weaknesses and strengths of respondents interviewing the user experience of the two applications where the Instagram application had more advantages than with the Snapchat application.